The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/978-3-319-15168-7_26
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Analysis of Toxic Behavior in an Online Video Game

Abstract: Abstract. In this paper we explore the linguistic components of toxic behavior by using crowdsourced data from over 590 thousand cases of accused toxic players in a popular match-based competition game, League of Legends. We perform a series of linguistic analyses to gain a deeper understanding of the role communication plays in the expression of toxic behavior. We characterize linguistic behavior of toxic players and compare it with that of typical players in an online competition game. We also find empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 6 publications
1
26
0
2
Order By: Relevance
“…Besides their competitive nature, MOBAs are also known for the complex social interactions they afford, with toxic player behavior among the major sources of negative experiences (Kwak and Blackburn, 2014;Kwak et al, 2015;Tyack et al, 2016). Tyack et al (2016), for instance, identified deviant behavior from teammates as a reason to abandon playing MOBA games, although most players ultimately quit due to reasons unrelated to the game.…”
Section: Moba Gamesmentioning
confidence: 99%
“…Besides their competitive nature, MOBAs are also known for the complex social interactions they afford, with toxic player behavior among the major sources of negative experiences (Kwak and Blackburn, 2014;Kwak et al, 2015;Tyack et al, 2016). Tyack et al (2016), for instance, identified deviant behavior from teammates as a reason to abandon playing MOBA games, although most players ultimately quit due to reasons unrelated to the game.…”
Section: Moba Gamesmentioning
confidence: 99%
“…The chat feature is designed for exchanging strategies and sharing emotions, and thus serves to foster a sense of belonging in the team. In practice however, it becomes a channel for toxic players to harass other ally players [32].…”
Section: Intra-group Conflicts and Socio-political Factorsmentioning
confidence: 99%
“…Most recently, another group of researchers observed that game interactions such as interacting with toxic players can have negative impacts on retention in League of Legends [19]. As cyberbullying has been considered as one of the factors that make players annoyed, feel fatigued, and even leave the game [15], there have been much efforts to define, detect, and prevent toxic playing in online games [4,13,14]. However, in this work, we do not investigate the effect of cyberbullying on player engagement due to the limitation of our dataset.…”
Section: Related Workmentioning
confidence: 99%